Pengaruh Pembangunan Jalan Lingkar Kota Pangkajene Terhadap Perubahan Pemanfaatan Lahan Sekitaranya di Kabupaten Pangkep (Studi Kasus Pemanfaatan lahan disepanjang jalan lingkar Kabupaten Pangkep) - Khalid, Abdul; Latief, Rudi; Taking, Muhammad Idris (Fakultas Teknik Universitas Bosowa, 2023)
To determine the effect of land use change on the intensity of land use change along the Pangkajene City ring road, Pangkep Regency and how land use patterns along the Pangkajene City ring road, in looking at changes in land use patterns in the next five years by identifying how much land use changes with observation time for five periods starting from 2007-2011. The analytical tools used are correlation tests to see the relationship between variables that are thought to influence and influence each other, and discriminatory discussions intended to provide explanations as they are based on the information and analysis results presented.